Comparison of clinicopathological characteristics of young and old North Indian patients of oral squamous cell carcinoma - G. Sharma; M. Kamboj; A. Narwal; A. Devi; J. Yadav; M. Sharma (Oral Oncology Reports)
Introduction: Oral squamous cell carcinoma (OSCC) ranks among the most prevalent epithelial malignancies in the head and neck region. Although it predominantly affects older individuals, there has been a concerning rise in incidence among the younger population in recent years. This study aimed to compare the clinicopathological features of OSCC at our institution distinguishing between young and older age groups. Methods: In the present retrospective study, histopathologically confirmed cases of OSCC were retrieved and assigned into two groups based on their age. Demographic data along with histopathological parameters were assessed. The data collected were statistically analysed using descriptive analysis, chi-square, kappa and multinomial logistic regression tests. A p-value less than or equal to 0.05 was considered statistically significant. Results: Of the 707 OSCC patients, 585 were over 40 years old, while 122 were 40 or younger. Both the groups exhibited comparable observations with a high degree of keratinization, moderate nuclear pleomorphism, type 3 pattern of invasion, low tumor budding, high stromal and low intratumoral infiltration of lymphocytes, except lymphoplasmacytic infiltrate which was marked in a higher number of young cases. Conclusion: OSCC in young and older individuals exhibited similar clinical as well as histopathological findings. Although the increased incidence of OSCC in the young is a cause of concern, so future multicentric studies with a larger sample size are warranted, to shed more light on the behavior and prognosis of OSCC in the young.